2015
DOI: 10.1021/acs.chemmater.5b03883
|View full text |Cite
|
Sign up to set email alerts
|

Water Infiltration in Methylammonium Lead Iodide Perovskite: Fast and Inconspicuous

Abstract: While the susceptibility of CH 3 NH 3 PbI 3 to water is well-documented, the influence of water on device performance is not well-understood. Herein, we use infrared spectroscopy to show that water infiltration into CH 3 NH 3 PbI 3 occurs much faster and at a humidity much lower than previously thought. We propose a molecular model in which water molecules have a strong effect on the hydrogen bonding between the methylammonium cations and the Pb−I cage. Furthermore, the exposure of CH 3 NH 3 PbI 3 to the ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
226
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(250 citation statements)
references
References 54 publications
18
226
5
1
Order By: Relevance
“…Experimental data and their interpretation, however, show strong variations. Spectroscopic results obtained from thin films depend on growth technique [29][30][31][32][33], grain size [30,34], and environmental conditions [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data and their interpretation, however, show strong variations. Spectroscopic results obtained from thin films depend on growth technique [29][30][31][32][33], grain size [30,34], and environmental conditions [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have described the effect of water during degradation of perovskite solar cells. 6,[17][18][19][20] It has been reported that water in the gas phase rapidly diffuses in perovskite films to generate hydrates via a two-step process starting with formation of MAPbI 3 ·H 2 O followed by (MA) 2 PbI 6 ·H 2 O after prolonged exposure to moisture. 17 A perfect understanding on the actual role of water during crystallization of the perovskite layer has been more elusive due to the high complexity of the system.…”
mentioning
confidence: 99%
“…For instance, M€ uller and co-workers showed that the reversible water infiltration into MAPbI 3 thin films occurs fast at a low relative humidity and increases the ionic conductivity remarkably. 40 Galisteo-Lopez et al reported that the photoluminescence (PL) of perovskites is better in oxygen rather than nitrogen conditions. 41 Similarly, Fang and coworkers showed a PL variation of MAPbBr 3 single crystals (MSCs) by exposing them to different gases.…”
mentioning
confidence: 99%
“…Specifically, those shallow trap states, caused by the reversible air (mainly O 2 and H 2 O) infiltration into MSCs, 40 could increase the PL but decrease the photocurrent of perovskite devices. Using first-principles computational analysis, several possible defect models are presented and verified according to the optical, electrical, and XRD results.…”
mentioning
confidence: 99%